PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN BENIH OKRA (Abelmoschus esculentus) LOKAL SUMBAWA SEBAGAI DASAR PENYUSUNAN BUKU PETUNJUK PRAKTIKUM FISIOLOGI TUMBUHAN - Edi Rustiawan; Husnul Jannah; Baiq Mirawati (Bioscientist : Jurnal Ilmiah Biologi, 2017)
ABSTRACT: In Indonesia, especially in West Nusa Tenggara Province, precisely in Sumbawa Island, this okra plant is very rarely used as a main crop in the agricultural world, but only used as plants with intercropping system. This matter cause less knowledge of okra plant, whereas agriculture area of Sumbawa island is very suitable for the development of okra cultivation is also less utilized by the society around, because some of society not yet know other mamfaat from okra plant (Abelmoschus esculentus). Okra content includes carbohydrates, proteins, vitamins A, B, C. The purpose of this is to determine the effect of planting media on the growth of okra plants (A. esculentus) and To develop the results of research on the okra planting medium (A. esculentus) Local Sumbawa as the basis preparation of the Physiology Practicum Guidebook Book I. held in Pejeruk Bangkat. On the number of leaves there are significant results due to the treatment of planting media of soil rice husk capable of absorbing water and tying her water in the soil in considerable amounts. Based on the validation of practical instructions, then this lab manual is suitable for use as a practicum of plant physiology.